Pendapatan Asli Daerah Pemerintah Kota di Jawa Timur - Avicenna Asyifyan, Mirza (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
Regional autonomy gives birth to independence, where a regional government is obliged to increase the potential for regional revenues to minimize its financial dependence on the central government. The aim of this research is to analyze the local revenue of city governments in East Java Province. Using panel data sourced from the Directorate General of Financial Balance, Ministry of Finance of the Republic of Indonesia for 2013-2022. The population of this research is 9 city governments in East Java Province, namely: Blitar, Kediri, Madiun, Malang, Mojokerto, Pasuruan, Probolinggo, Surabaya and Batu. The research approach is quantitative with descriptive research type. The systematic analysis of research data uses 3 stages, namely: normality test, t test (one sample) and hypothesis testing using SPSS. By analyzing the One-Sample Test data, this research is also directed at testing the hypothesis, namely: the original regional income of the city government in East Java Province is 26 (high). The results of the research found that the research hypothesis was not tested so that in the period or period of observation, the original regional income of the city government in East Java was in a high position. Keywords: Locally-generated revenue; Regional autonomy; Regional Financial Performance